A dense 3d–4f metal–organic framework with "gas pockets" for highly efficient CH4/N2 separation. Issue 8 (24th March 2023) - Zhu, Li-Min; Li, Wen-Liang; Li, Tian-Ran; Shi, Lin-Ping; Li, Li-Ting; Yao, Zhao-Quan; Huang, Hong-Liang; Zhao, Jiong-Peng; Liu, Fu-Chen
Abstract : A pillar-layered dense 3d–4f MOF shows high IAST selectivity for CH4 /N2 owing to the enhancement of the interactions between the MOF and CH4 by the heteroatoms of the pillars. Abstract : In this work, we report a multi-component MOF [CuCe L(Cl4 -bdc)0.5 (H2 O)2 ·(H2 O)6 ] n (L = 1 H -pyrazole-3, 4, 5-tricarboxylic acid, Cl4 -bdc = 2, 3, 5, 6-tetrachloroterephthalate) with a pillar-layered structure. In the structure, the polydentate ligand (L) linked Cu II and Ce III atoms constitute 3d–4f layers that serve as the pedestal base and the chlorinated Cl4 -bdc ligands acting as bolsters are installed between the layers through Ce III . The moderate pore size and the unique chloride decorated surface of channels endow this MOF with excellent separation ability for methane (CH4 ) and nitrogen (N2 ). According to the adsorption tests, this MOF exhibits a high adsorption capacity for CH4 (28.41 cm 3 /cm 3 ) at 298 K and 1 bar, while the N2 adsorption capacity is only 3.43 cm 3 /cm 3 . The DFT calculations demonstrate that the adjacent Cl4 -bdc in the network can act as "gas pockets" or nano traps to immobilize the CH4 molecules effectively through multiple interactions between Cl atoms and CH4 . The high performance of this MOF in CH4 /N2 separation has been verified by the outstanding IAST selectivity of 13.32 and breakthrough experiments. This work provides a new perspective for capturing CH4 from coal-mine gas to recover fuel and reduce greenhouse gas emissions.